The effect of a training program on the development of some social skills for the physically handicapped (Journal of the College of Basic Education, 2022)
Research goals and hypotheses:The current research aims to:1- Measuring the social skills of the physically disabled.2- Preparing a training program to develop the social skills of the physically handicapped.3- Knowing the impact of the training program on developing the social skills of the physically handicapped.To verify the third objective, the researcher puts the following hypothesis:There are no statistically significant differences at the significance level (0.05) between the scores of the experimental group members before and after applying the training program.